2018
DOI: 10.22226/2410-3535-2018-2-225-230
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic phase transformation in NiTi bi-crystals with symmetric ∑25 twist and tilt grain boundaries

Abstract: NiTi alloys attract a lot of attention of researchers for a number of reasons; among them are their practical importance and challenges for theoretical understanding. The most exciting feature of these alloys is the shape memory effect due to the martensitic transformation at temperatures close to the room temperature. There exist many factors affecting the transition temperatures in such materials, such as a deviation from stoichiometric composition, dislocation density, grain size, and the type of grain boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The experimental studies have shown that the grain boundaries (GBs) and triple junctions (TJs) are additional heterogeneities favourable for the M nucleation in the polycrystalline samples of such phase-changing materials [27][28][29][30][31][32][33][34][35][36][37], which was also confirmed through atomistic simulations [38][39][40][41][42]. In particular, the parameters such as the grain orientation distribution (see, e.g.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…The experimental studies have shown that the grain boundaries (GBs) and triple junctions (TJs) are additional heterogeneities favourable for the M nucleation in the polycrystalline samples of such phase-changing materials [27][28][29][30][31][32][33][34][35][36][37], which was also confirmed through atomistic simulations [38][39][40][41][42]. In particular, the parameters such as the grain orientation distribution (see, e.g.…”
Section: Introductionmentioning
confidence: 78%
“…The temperatures of M nucleation from the GBs are usually significantly higher than the homogeneous transformation temperature of M [28,29]. The start and finish temperatures for both the forward (A → M) and the reverse (M → A) transformations from the tilt GBs are much higher than that for the twist GBs [28,32,38,39]. The reason for this was attributed to the local stress fields associated with the intrinsic dislocations in the low angle tilt GBs [28,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the current work aims to study the effect of Ni and Ti segregations to Σ25 tilt GBs of NiTi bi-crystals on MT characteristic temperatures by means of the molecular dynamics simulations. This paper can be regarded as a continuation of our previous work devoted to NiTi bi-crystals having tilt or twist GBs without segregations [39], and therefore it will be focused on the effect of GB segregations of Ni and Ti on MT temperatures in comparison with our previous results.…”
Section: Introductionmentioning
confidence: 93%
“…MD simulation of the equiatomic alloy without GB segregation is conducted for a computational cell in the form of rectangular parallelepiped that was used in our previous work [39]. Ni and Ti atoms of the rectangular cell (12.8 × 4.0 ×12.8 nm 3 ) form two B2 crystals separated by the symmetric Σ25 (710) tilt GBs with the <010> misorientation axis (Fig.…”
Section: Modelingmentioning
confidence: 99%